2022
DOI: 10.3390/antiox11091732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermally-Oxidized Frying Oils (Corn Oil and Lard) on Gut Microbiota in Hamsters

Abstract: Repeated reuse of frying oil raises health concerns due to the accumulation of oxidative products after each frying cycle. Gut microbiota is integral in lipid metabolism and immune regulation. The present study was designed to investigate the effects of thermally-oxidized corn oil and lard on gut microbiota in relation to atherosclerosis, inflammatory cytokines, and plasma lipids. Male Golden Syrian hamsters were randomly divided into four groups and fed one of four diets containing fresh corn oil (CF), oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The Shannon index analysis showed that the richness and diversity of gut microbiota in the MD and HD groups were significantly reduced at 6d, which is consistent with the results of a previous study in mice fed fried corn oil and lard for six weeks [14].…”
Section: Discussionsupporting
confidence: 90%
“…The Shannon index analysis showed that the richness and diversity of gut microbiota in the MD and HD groups were significantly reduced at 6d, which is consistent with the results of a previous study in mice fed fried corn oil and lard for six weeks [14].…”
Section: Discussionsupporting
confidence: 90%
“…47 In recent years, it has been reported that that frying oil adversely regulated the gut microbiota and exacerbated atherosclerosis in hypercholesterolemic hamster models. 48 Additionally, our laboratory has conducted studies showing that polar compounds generated during the high-temperature oxidation of oil can result in liver damage and disruption of the intestinal barrier. 16,18 These findings indicate that thermo-induced oxidized oil is a serious health hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in blood urea nitrogen, serum CR, URE, UA, and glucose levels with reduced levels of total protein, albumin, and globulin along with changes in serum electrolyte concentrations, such Na, K, Mg, and Ca, show tissue toxicity and damage to visceral organs. Similarly (Kwek et al, 2022) reported that regular intake of deep-fried corn oil and lard could affect gut health (Aziz et al, 2024, Aziz et al, 2023a. A previous research conducted by (Baig et al, 2022) also demonstrated similar results.…”
Section: Recommendationmentioning
confidence: 99%